On the Origin of the Magnetic Concentration Gradient Force and Its Interaction Mechanisms with Mass Transfer in Paramagnetic Electrolytes - Magne Waskaas (Fluids, 2021)
The objective of this work is to analyze the origin of the magnetic concentration gradient force. The force will be studied in a diffusion system where a paramagnetic electrolyte diffuses through a thin, inert membrane under the influence of a homogeneous magnetic field. The force will be analyzed using the theory of magnetic circuits, i.e., by the concept of minimum reluctance principles. In addition, based on some previous studies, it will be discussed whether the minimum reluctance principle can be applied to mass transfer into and out of the diffusion layer at electrode/electrolyte interfaces. The results show that the magnetic concentration gradient force arises as a consequence of the minimum reluctance principle. Applied to the diffusion system, the magnetic concentration gradient force arises in the membrane as a consequence of the concentration gradient and hence, the reluctance gradient. The force acts on the flow in such a way that the reluctance in the membrane is minimized. The force implies two interaction mechanisms: attraction of the paramagnetic electrolyte flowing into the membrane in order to decrease the reluctance, and hindrance of the paramagnetic electrolyte flowing out of the membrane in order to hinder an increase in the reluctance. Based on previous studies, it is shown that the minimum reluctance principle can be applied to mass transfer into or out of the diffusion layer at electrode/electrolyte interfaces as well.